Pengaruh Pemberian Insentif Dalam Menigkatkan Kinerja Karyawan PT. Win Wahana Cipta Marga di Makassar - Aprisia Alma; Jeane Tandirerung; Kordiana Sambara (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
This study explains that the main objective of the study is to understand the effect of providing incentives in improving the performance of employees of PT Win Wahana Cipta Marga in Makassar. that incentives can be an effective tool to increase employee motivation and work performance in the company This research uses quantitative methods with primary data sources and data collection through questionnaires. The analysis technique in this study uses the correlation coefficient test, spearman coefficient, validity test, determinant coefficient and T test. The results of the analysis show that providing incentives has a significant effect on employee performance, which means 0.001> 0.05 then Ho is accepted and H1 is rejected.